2006
DOI: 10.1242/dev.02455
|View full text |Cite
|
Sign up to set email alerts
|

Prdm1 acts downstream of a sequential RA, Wnt and Fgf signaling cascade during zebrafish forelimb induction

Abstract: There were mistakes in the Materials and methods 'Treatment with DEAB, SU5402' section on p. 2806 of this paper. The whole section should therefore be replaced with the following.4-Diethylaminobenzaldehyde (DEAB) (Fluka) and the FGF receptor inhibitor SU5402 (Calbiochem) were dissolved in dimethylsulfoxide (DMSO) and used at a concentration of 10 M and 16 M, respectively. DEAB treatment was performed from 30% epiboly onwards.Incubations were carried out in the dark at 28°C. The authors apologise to readers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
121
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(133 citation statements)
references
References 59 publications
12
121
0
Order By: Relevance
“…However, no observation of prdm1a was in the primordial germ cells (PGCs) of medaka. These results hinted that medaka Prdm1a possibly has similar function as its homologues of zebrafish and mouse in development of muscle [38,46], neural crest [41,46], branchial arches [46], fin [43,44,46], eye [29,55], intestine [30,31], heart [28] and bone [56]. In mouse, Prdm1 plays its role itself and/or through its partner factors, Prmt5 and/or Groucho proteins [9,25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, no observation of prdm1a was in the primordial germ cells (PGCs) of medaka. These results hinted that medaka Prdm1a possibly has similar function as its homologues of zebrafish and mouse in development of muscle [38,46], neural crest [41,46], branchial arches [46], fin [43,44,46], eye [29,55], intestine [30,31], heart [28] and bone [56]. In mouse, Prdm1 plays its role itself and/or through its partner factors, Prmt5 and/or Groucho proteins [9,25].…”
Section: Discussionmentioning
confidence: 91%
“…Zebrafish prdm1a is expressed in the visceral endoderm, anterior endomesoderm and the prechordal plate of gastrula stage embryos, and is expressed in pharyngeal arches, limb buds, otic vesicles, photoreceptor cell layer, slow muscle and cloaca later in development [41]. Prdm1a plays major roles in dorsal-ventral patterning in zebrafish embryos [41] and is required for specification of the slow-twitch muscle lineage [38,42], branchial arches [41], pectoral fin [41,43,44], neural crest and sensory neuron progenitors [45,46] in zebrafish. However, the role of Prdm1 in fish immune system is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, Tbx5a might regulate a convergence cue located within the posterior half of the fin-field. One candidate is fgf24, a Tbx5a target that is required for the coalescence of Tbx5a + cells and formation of the pectoral fin Fischer et al, 2003;Mercader et al, 2006). fgf24 is expressed in a more restricted domain within the posterior position in the tbx5a + LPM (Fischer et al, 2003), roughly aligned with the future position of the prospective fin bud ( Fig.…”
Section: Fgf24 Functions As a Posterior Convergence Cue For Fin-fieldmentioning
confidence: 99%
“…RA has long been known to be able to influence patterning of regenerating and developing limbs (Maden, 1982;Tickle et al, 1982) while its involvement in limb initiation has been suggested only in recent years (Grandel et al, 2002;Mic et al, 2004;Gibert et al, 2006;Mercader et al, 2006;Zhao et al, 2009). RA is synthesized from its precursor retinal that is maternally supplied to the zebrafish egg (Costaridis et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…But when and where does RA come into play? While all studies agree that the competence of the lateral plate mesoderm to respond to RA with limb/fin development extends up to mid-somitogenesis in the mouse and fish, different conclusions have been reached on the timing of the endogenous RA signaling event that leads to limb/fin precursor determination and, consequently, to tbx5 expression: Determination of forelimb/pectoral fin precursors has been proposed to require RA signaling from the margin and/or the paraxial mesoderm of the zebrafish embryo either before somitogenesis (Grandel et al, 2002) or from trunk somites during early somitogenesis stages (Gibert et al, 2006;Mercader et al, 2006;Zhao et al, 2009). Importantly, Zhao and coworkers showed results of rescue experiments in mouse aldh1a2 mutants that suggest lack of RA signaling in the prospective limb precursors and early forelimb buds during early somitogenesis (Zhao et al, 2009), a result compatible with limb precursor determination before somitogenesis.…”
Section: Introductionmentioning
confidence: 99%